Characterization of the Complete Mitochondrial Genomes of Two Sibling Species of Parasitic Roundworms, Haemonchus contortus and Teladorsagia circumcincta - Palevich, Nikola; Maclean, Paul H.; Choi, Young-Jun; Mitreva, Makedonka (Frontiers in Genetics, 2020)
Haemonchus contortus and Teladorsagia circumcincta are among the two most pathogenic internal parasitic nematodes infecting small ruminants, such as sheep and goats, and are a global animal health issue. Accurate identification and delineation of Haemonchidae species is essential for development of diagnostic and control strategies with high resolution for Trichostrongyloidea infection in ruminants. Here, we describe in detail and compare the complete mitochondrial (mt) genomes of the New Zealand H. contortus and T. circumcincta field strains to improve our understanding of species- and strain-level evolution in these closely related roundworms. In the present study, we performed extensive comparative bioinformatics analyses on the recently sequenced complete mt genomes of the New Zealand H. contortus NZ_Hco_NP and T. circumcincta NZ_Teci_NP field strains. Amino acid sequences inferred from individual genes of each of the two mt genomes were compared, concatenated and subjected to phylogenetic analysis using Bayesian inference (BI), Maximum Likelihood (ML) and Maximum Parsimony (MP). The AT-rich mt genomes of H. contortus NZ_Hco_NP and T. circumcincta NZ_Teci_NP are 14,001 bp (A+T content of 77.4 %) and 14,081 bp (A+T content of 77.3 %) in size, respectively. All 36 of the typical nematode mt genes are transcribed in the forward direction in both species and comprise of 12 protein-encoding genes (PCGs), 2 ribosomal RNA (rrn) genes, and 22 transfer RNA (trn) genes. The secondary structures for the 22 trn genes and two rrn genes differ between H. contortus NZ_Hco_NP and T. circumcincta NZ_Teci_NP, however the gene arrangements of both are consistent with other Trichostrongylidea sequenced to date. Comparative analyses of the complete mitochondrial nucleotide sequences, PCGs, A+T rich and non-coding repeat regions of H. contortus NZ_Hco_NP and T. circumcincta NZ_Teci_NP further reinforces the high levels of diversity and gene flow observed among Trichostrongylidea, and supports their potential as ideal markers for strain-level identification from different hosts and geographical regions with high resolution for future studies. The complete mt genomes of H. contortus NZ_Hco_NP and T. circumcincta NZ_Teci_NP presented here provide useful novel markers for further studies of the meta-population connectivity and the genetic mechanisms driving evolution in nematode species.